The Influence of Service Quality and Brand Image on Customer Loyalty at the Post Office in Batam City - Syahrul Bahri (International Journal Labs, 2025)
This study aims to investigate and examine the influence of Service Quality and Brand Image on Customer Loyalty at the post office in Batam City, specifically regarding the use of parcel delivery services. This research uses primary data, with a sample of 100 respondents who are customers at post offices in Batam City (2025). A questionnaire was used to collect the data, and SPSS version 25 was employed as the analytical tool. Based on the research findings, the decision to use the post office’s delivery services in Batam City is primarily influenced by Customer Loyalty. Meanwhile, Service Quality and Brand Image have a positive but not significant impact. However, Customer Loyalty in using the post office’s parcel delivery services in Batam City is significantly influenced by the cumulative effect of Service Quality, Brand Image, and Customer Loyalty. The novelty of this study lies in its context, as previous research on Customer Loyalty in the logistics and delivery service sector in Indonesia has primarily focused on private courier companies, while studies on state-owned enterprises such as post offices remain limited. By analyzing the interplay of Service Quality, Brand Image, and loyalty in the public postal sector, this research provides a new perspective on how traditional service providers can remain competitive in the digital era, where private couriers and e-commerce platforms dominate.